“Softsciences”: a Portuguese project on computers for learning basic sciences - Paiva, João Carlos (2000)
We present the «Softsciences» project, a common action undertaken by the Portuguese Physical, Chemical and Mathematical Societies since 1991. Its goal is creating, producing and distributing software for learning Science and Mathematics, at the middle and high school levels. We describe some products we have made and our future plans, for both off- and on-line edition. Experiences like ours promoting a synergy of secondary and tertiary schools to produce discipline-based computational materials are effective means for improving science education